Hand waving in command spaces: a framework for operating home appliances. (17th September 2018) - Kano, Takumi; Kawamura, Takuya; Asano, Hidetsugu; Nagayasu, Takeshi; Umeda, Kazunori
ABSTRACT: In this paper, hand waving in a 'command space' is proposed as a new framework for operating home appliances. A command space is associated with the operation of a home appliance; an operation is retrieved by waving a hand in the command space. A home appliance operation system with the function of multiplexing command space modules and integrating multiple commands is constructed. With the proposed framework and system, home appliance operation is possible only by hand waving, an intuitive gesture for a human. Experiments were conducted that verified that complex operations, such as scheduling the recording of a TV program, can be performed with the system. The usability of the constructed system is evaluated using Brooke's System Usability Scale (SUS). The average SUS score was 66.8, which indicates that the subjects had relatively positive impression on the system in spite of long operation time. GRAPHICAL ABSTRACT: